Reading Thomas Bernhard’s "The Basement" from anthropology - Ezpeleta Pérez, Antonio (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This paper proposes a reading of the autobiography of Thomas Bernhard, in particular of his second volume, The Basement. From an anthropological perspective, it studies the exposition of his life trajectory, which culminates in his desire to separate himself from a society that he fiercely criticizes.